Exploration of sea anemone-inspired high-performance biomaterials with enhanced antioxidant activity - Lulu Wang (KeAi Communications Co., Ltd., 2022)
Antioxidant biomaterials have attracted much attention in various biomedical fields because of their effective inhibition and elimination of reactive oxygen species (ROS) in pathological tissues. However, the difficulty in ensuring biocompatibility, biodegradability and bioavailability of antioxidant materials has limited their further development. Novel bioavailable antioxidant materials that are derived from natural resources are urgently needed. Here, an integrated multi-omics method was applied to fabricate antioxidant biomaterials. A key cysteine-rich thrombospondin-1 type I repeat-like (TSRL) protein was efficiently discovered from among 1262 adhesive components and then used to create a recombinant protein with a yield of 500 mg L−1. The biocompatible TSRL protein was able to self-assemble into either a water-resistant coating through Ca2+-mediated coordination or redox-responsive hydrogels with tunable physical properties. The TSRL-based hydrogels showed stronger 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging rates than glutathione (GSH) and ascorbic acid (Aa) and protected cells against external oxidative stress significantly more effectively. When topically applied to mice skin, TSRL alleviated epidermal hyperplasia and suppressed the degradation of collagen and elastic fibers caused by ultraviolet radiation B (UVB) irradiation, confirming that it enhanced antioxidant activity in vivo. This is the first study to successfully characterize natural antioxidant biomaterials created from marine invertebrate adhesives, and the findings indicate the excellent prospects of these biomaterials for great applications in tissue regeneration and cosmeceuticals.